"Sticky" carbon coating enables high-area-capacity lithium storage of silicon-graphitic carbon hybrid. (30th October 2021) - Chen, Zidong; Li, Lun; Zhang, Zheng; Li, Hao; Xie, Bo; Chen, Yungui; Davoodi, Ali; Hosseinpour, Saman; Liu, Wei
Abstract: Pulverization and surface instability have been identified as the main impediments to the application of Si anodes in high-energy lithium-ion batteries (LIBs). In this study, a Si-graphitic carbon hybrid (SiG) is created via embedding Si nanoparticles in between expanding graphite interlayers, thus to be adopted as a model system to unravel structure-properties relations for LIBs applications. We explore the impact of artificial surface coating layers on the lithium cycling performance of SiG particles. In comparison with native SiG and carbon-coated SiG (CC-SiG), we find that the "sticky-carbon" coating, i.e., an epoxy-rich layer on top of the carbon coating, gave rise to superior cycle performance. In the "sticky carbon" coated SiG (SCC-SiG), the surface chemistry appears to have a pivotal role in both alleviating electrode disintegration and forming a favorable SEI rich in fluorine-polymers. These positive findings are examined in electrodes with mass loading ranging from 1.0 to 5.0 mg/cm 2, achieving area capacities up to ∼5.0 mAh/cm 2 . A full cell adopting >6 mg/cm 2 LiNi0.8 Co0.1 Mn0.1 O2 (NCM811) cathode and SCC-SiG delivers stable cycling performances. It is hence unraveled that the carbon coating layer with reactive surface groups on the top is an unrecognized key for wide range of Si-based anodes. Graphical abstract: Image 1 Highlights: A novel "sticky" carbon coating was developed for silicon-carbon composite. SEI composition and particle-binder bonding are both pivotal for cycle performances. "Sticky" carbon coating alleviates cycled-induced electrode swelling and cracking. High area capacity (5 mAh/cm 2 ) cycle performances were achieved.